Role of Epileptic Activity in Older Adults With Delirium, a Prospective Continuous EEG Study - Sambin, Sara; Gaspard, Nicolas; Legros, Benjamin; Depondt, Chantal; De Breucker, Sandra; Naeije, Gilles (Frontiers in Neurology, 2019)
Background/Objectives: Delirium occurs in up to 50 % of hospitalized old patients and is associated with increased morbidity and mortality. Acute medical conditions favor delirium, but the pathophysiology is unclear. Preliminary evidence from retrospective and prospective studies suggests that a substantial minority of old patients with unexplained delirium have non-convulsive seizures or status epilepticus (NCSE). Yet, seeking epileptic activity only in unexplained cases of delirium might result in misinterpretation of its actual prevalence. We aimed to systematically investigate the role of epileptic activity in all older patients with delirium regardless of the underlying etiology. Design, Setting: Prospective observational study in a tertiary medical center. Adults >65 years with delirium underwent at least 24 h of continuous electro-encephalographic monitoring (cEEG). Background patterns and ictal and interictal epileptic discharges were identified, as well as clinical and biological characteristics. Participants: Fifty patients were included in the study. Results: NCSE was found in 6 (12%) patients and interictal discharges in 15 (30%). There was no difference in the prevalence of epileptic activity rates between delirium associated with an acute medical condition and delirium of unknown etiology. Conclusion: Epileptic activity may play a substantial role in the pathophysiology of delirium by altering brain functioning and neuronal metabolism. No clinical or biological marker was found to distinguish delirious patients with or without epileptic activity, underlining the importance of cEEG in this context.